Efektivitas Pengelolaan Badan Usaha Milik Nagari Karya Anak Nagari dalam Meningkatkan Pendapatan Nagari di Nagari Pinaga Aua Kuniang Kabupaten Pasaman Barat - Abdi Satrianto; Hasbullah Malau (Lembaga Yasin AlSys, 2026)
Nagari-Owned Enterprises (BUMNag) were established as instruments to optimize the economic potential of nagari and increase Nagari Own-Source Revenue in accordance with Government Regulation Number 11 of 2021. However, the management of the laying-hen farming business unit operated by BUMNag Karya Anak Nagari in Nagari Pinaga Aua Kuniang, West Pasaman Regency, has faced declining egg sizes, rising feed costs, and fluctuating profits, while previous studies have focused primarily on trading and service business units. This study aimed to analyze the effectiveness of BUMNag Karya Anak Nagari’s management in increasing nagari revenue and to identify its supporting and inhibiting factors. The study employed a descriptive qualitative approach involving 10 informants selected through purposive sampling, consisting of the Wali Nagari, the BUMNag Director, the farm manager, a farm worker, and six nagari residents. Data were collected through interviews, observation, and documentation and were subsequently analyzed based on Duncan’s three effectiveness indicators in Steers, namely goal attainment, integration, and adaptation. The results showed that BUMNag management had been implemented but was not yet fully effective. The production of large eggs decreased by 30.99% from January to June 2026, whereas the proportion of small eggs increased from 12.28% to 32.74% during the same period. The business unit’s net profit also declined from IDR 7,900,000 to IDR 1,444,900, while its contribution to Nagari Own-Source Revenue remained inconsistent because it was recorded in detail for only two of the six months observed. Supporting factors included support from the nagari government, the division of responsibilities among management personnel, and strong community demand for eggs, whereas inhibiting factors included high feed costs, limited capital, and the absence of standard operating procedures for farm management. This study concluded that the effectiveness of BUMNag management needs to be improved through production cost control, capital strengthening, the development of standard operating procedures, and improvements in financial recording and contributions to Nagari Own-Source Revenue. These findings provide practical contributions to the nagari government and BUMNag management in sustainably improving the governance of livestock business units.